Pengaruh Kepemilikan Institusional, Kebijakan Hutang dan Kebijakan Dividen terhadap Nilai Perusahaan - Wisyandri, Adhe Alvita; Ardaninggar, Sasmita Sari (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study examines the effect of institutional ownership, debt policy, and dividend policy on firm value, with firm size and firm growth as control variables. The issue addressed is that firm value, as reflected in stock performance, is influenced by internal and external financial decisions, yet previous studies show mixed results, especially in the financial sector. The research aims to provide empirical evidence on whether these governance and financial policies significantly shape firm value. The population consists of 106 financial sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using purposive sampling, 18 firms were selected, resulting in 90 firm-year observations. Data were analyzed with EViews 13 through descriptive statistics, classical assumption tests, and panel regression analysis. The findings reveal that institutional ownership, debt policy, and dividend policy simultaneously have a significant impact on firm value. Partially, institutional ownership does not significantly influence firm value, while debt policy and dividend policy show significant positive effects. These results highlight the importance of debt management and dividend distribution in enhancing firm value in the Indonesian financial sector.